A FEATURE FILM IN A RUSSIAN LANGUAGE CLASS WITH FOREIGN CADETS (ON THE EXAMPLE OF THE FILM "ONLY "OLD MEN" GO INTO BATTLE") - Gladkikh I. A., Parfionova T. A. (Socio-Pedagogical Issues of Education and Upbringing, 2022)
The article is devoted to the use of feature films in the course of Russian as a foreign language in a military university. Using films in Russian as a foreign language course allows cadets to improve their skills in all types of speech activity, contributes to the formation of their cultural competence, as well as increase interest and motivation to study Russian language. The work with the film is considered on the example of the movie "Only "old men" go into battle".
Keywords: русский язык как иностранный; лингвокультурологическая компетенция; социокультурная адаптация; socio-cultural adaptation; Russian as a foreign language; художественный фильм; иностранные курсанты; feature film; foreign cadets; linguistic and cultural competence